THE RELATIONSHIP OF DIET AND PHYSICAL ACTIVITIES WITH THE INCIDENCE OF HYPERTENSION AMONG THE ELDERLY IN THE RW 05 AREA OF BABAKAN PARI VILLAGE, EAST BATUJAJAR VILLAGE, 2022 - Rinarmi, Rinarmi; Khatijah, Siti (Lux Mensana: Journal of Scientific Health, 2024)
Introduction : Hypertension or high blood pressure is a condition where systolic blood pressureincreases to more than or equal to 140 mmHg and diastolic blood pressure to more than or equalto 90 mmHg . Hypertension in the elderly is something that is often found because most middleaged or elderly people are at risk of developing hypertension. A person is said to be elderly if heis 60 years or older, whether male or female . The 2018 Riskesdas results show that theprevalence of the population with high blood pressure is 34.11% . In 2018, West Java rankedsecond as the province with the highest cases of hypertension in Indonesia, namely 39.6%.According to data from the West Bandung District Health Service , disease with amount highestthat is hypertension . Lack of physical activity increases the risk of suffering from hypertension.Meanwhile, physical activity is the movement carried out by the muscles and their supportingsystems. During physical activity, muscles require energy outside metabolism to move. Anotherfactor that causes hypertension in the elderly is poor diet. Diet is the method or behavior adoptedby a person in selecting and using food ingredients in daily food consumption which includes thetype of food, amount of food and frequency of eating. Method : used in this research iscorrelation research using a cross sectional approach. Amount sample in study This as many as80 elderly people. Result & Analysis : Statistical test results with using the chi-square test Forpattern Eat obtained p value (0.000) < α (0.05) and for activity physique obtained p value (0.040)< α (0.05) then H0 is rejected. Discussion : With thereby can concluded that there is connectionpattern eating and activities physique with incident hypertension in the elderly in the RW 05Kampung Babakan Pari area, East Batujajar Village. Therefore, there needs to be efforts fromthe Community Health Center to maintain the continuity of promotive and preventive effortswhich is carried out for a minimum of 3 months, especially those related to diet and how toprevent hypertension.